The Effects of Neuro-Developmental Treatment Based Rehabilitation on Gross Motor Function in Spastic Cerebral Palsy Children Rehabilitation - Duygu Çubukçu; Pakize Karaoğlu (Galenos Publishing House, 2020)
INTRODUCTION: The aim of the study was to assess gross motor progress in children with spastic cerebral palsy treated with neurodevelopmental treatment-based rehabilitation. METHODS: Out of 30 patients with spastic cerebral palsy (diplegia, quadriplegia) aged 2-5 years, 15 patients were assigned to neurodevelopmental treatment-based rehabilitation group (group A), whereas 15 patients were assigned to convansionel home exercises programme (group B). The neurodevelopmental treatment-based rehabilitation group received three sessions of neurodevelopmental treatment 60 minutes per day, three times per week, for 3 months in an outpatient setting. The intervention programme was administered for 3 months. Gross motor function was assessed using the Gross Motor Function Measure 88 (GMFM-88), before treatment and after treatment. RESULTS: At baseline, there were no statistically significant difference between the two groups with respect to age, sex, clinic type and GMFM-88 values. After 3 months; there were no significant differences between two groups regarding the total scores of GMFM-88 (p>0.05) whereas significant difference was found between the sitting, crawling and kneeling, standing, walking-running-jumping dimensions of the gorups. (p<0.001). After 3 months, all dimensions of GMFM-88 were significantly increased in group A (p<0.001). Standing, walking-running-jumping dimensions showed no statistically significant difference in group B (p > 0.05). DISCUSSION AND CONCLUSION: The neurodevelopmental treatment contributes to all areas of rough motor function in children with spastic cerebral palsy. Neurodevelopmental treatment is promising and randomized controlled further studies are needed for rehabilitation technics.